Aplikasi Virtual Reality Sebagai Media Promosi Rumah Adat Minahasa : Virtual Reality as Promotional Media for Minahasa Traditional Houses - Yuri V. Akay; Kenneth Palilingan; Salvius P. Lengkong (Jurnal Teknik Informatika, 2024)
Minahasa traditional houses are one of the interesting tourist attractions for tourists who are interested in the culture and history of the North Sulawesi region. Virtual reality (VR) is the latest technology that provides a different experience in interacting with the digital environment. In the promotional field, VR is an attractive alternative for presenting more realistic and interactive visual content. The aim of this research is to develop a mobile Virtual Reality software for Minahasa traditional houses. This application is designed to make it easier for users to experience direct interactive experiences from Minahasa traditional houses using VR technology. In this research, a number of stages will be carried out, namely literature study, data collection, system design, system creation, testing and evaluation.